ANALISA PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP FINANCIAL PERFORMANCE MELALUI CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY SEBAGAI VARIABEL INTERVENING DI PERUSAHAAN PERBANKAN DI SURABAY - Tanzi, Clarissa (Business Accounting Review, 2015)
The purpose of this study is to determine whether there are significant implementation of Transformational leadership towards financial performance through customer satisfaction and customer loyalty as intervening variable in banking corporate at Surabaya. The sample used in this study are banking corporate listing on Bursa Efek Indonesia(BEI). Data analysis using Partial Least Square method on 600 respondents from 35 selected banks in Surabaya. The result of this study demonstrate that transformational leadership has positive effect on financial performance